Polymer Free Volume Effects on Protein Dynamics in Polystyrene Revealed by Single-Molecule Spectroscopy - Moringo, Nicholas A (Langmuir : the ACS journal of surfaces and colloids, 2020)
Protein-polymer interactions are critical to applications ranging from biomedical devices to chromatographic separations. The mechanistic relationship between the microstructure of polymer chains and protein interactions is challenging to quantify and not well studied. Here, single-molecule microscopy is used to compare the dynamics of two model proteins, α-lactalbumin and lysozyme, at the interface of uncharged polystyrene with varied molecular weights. The two proteins exhibit different surface interaction mechanisms despite having a similar size and structure. α-Lactalbumin exhibits interfacial adsorption-desorption with residence times that depend on polymer molecular weight. Lysozyme undergoes a continuous time random walk at the polystyrene surface with residence times that also depend on the molecular weight of polystyrene. Single-molecule observables suggest that the hindered continuous time random walk dynamics displayed by lysozyme are determined by the polystyrene free volume, a finding supported by thermal annealing and solvent quality studies. Hindered dynamics are dominated by short-range hydrophobic interactions where the contributions of electrostatic forces are negligible. This work establishes a relationship between the microscale structure (i.e., free volume) of polystyrene polymer chains to nanoscale interfacial protein dynamics